Data on in vitro effects of eflornithine against trypanosoma parasites - Boberg, Mikael (University of Gothenburg, 2021)
The study aimed to investigate the pharmacological effects of the drug eflornithine against parasites in vitro. AlamarBlue serial drug dilution assay was used to quantify parasite growth inhibition and a ﬂuorescence scanner was used to read the 96 well plates. Values from the readings are presented in the corresponding datasets where "Assay ID" shows which plate was analysed.

Data on in vitro effects of eflornithine against trypanosoma parasites including time-dependent data and in vitro effect on L6 cells

Syftet med studien var att studera läkemedlet eflornitins effekter på parasiter in vitro. Metoden "AlamarBlue serial drug dilution assay" användes för att kvantifiera hämningen av parasittillväxt och 96-hålsplattorna analyserades av en ﬂuorescence-scanner. Dessa värden finns i tillhörande dataset där "Assay ID" indikerar vilken platta som analyserats.

Data för in vitro-effekt av eflornitin mot trypanosoma-parasiter inklusive data för tidsberoende effekter och data på effekterna mot L6 cell in vitro
Data för in vitro-effekt av eflornitin mot trypanosoma-parasiter
Keywords: Dose-Response Relationship, Drug; Dosrelaterad effekt av läkemedel; Pharmacology and Toxicology; Farmakologi och toxikologi